Children’s right to digital safety : evaluating the way by which the law can increase effective protection for children in South Africa - Fokala, Elvis (University of Pretoria, 2024)
Mini Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2024.